Análise Técnico-económica das Soluções Construtivas Utilizadas na Reabilitação de Escolas - Filipe Manuel Carvalho Torres (2012)
School is the ideal place for acquiring knowledge and tools to build the future. Together with environmental and energy efficiency concerns, emerges the need for a strategic investment on the rehabilitation of Portuguese school buildings. This dissertation aims to discuss the rehabilitation solutions available for schools, through both a sensitivity analysis and an economic point of view, on a selected case-study. The sensitivity analysis is based on a multi-objective optimization procedure, for which Artificial Neural Networks were the instrument used to approximate the simulation results. For the second analysis and from an economic perspective, the model of analysis was Life Cycle Cost. The results point towards the importance of RPH on the school's building environmental performance, when it comes to energy for heating and overheating on the colder season. Secondly, the influence of the economic scenario was evident on the optimization of wall and roof insulation. The case-study on school rehabilitation proved to be of high energy consumption, used for heating, due to the designed number of renovations per hour. In sum, the present study contributes to a better understanding of the school's building performance and to more sustained future decisions on the rehabilitation of schools, by the decision-makers. Keywords: Thermal, Confort, cost, energy, schools.